Distributed Panel-based Fire Alarm Design - Anggara Trisna Nugraha; Moch Fadhil Ramadhan; Muhammad Jafar Shiddiq (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2022)
The shopping center switchboard system consists of several parts: a 20 kV cabinet to a 20 kV to 380 V step-down transformer, which is then provided to the user to control the newly upgraded LVMDP (low voltage main switchboard). Before distributing to users, they need to pay attention to the fixed power factor of the capacitor bank. Lack of an exemplary power factor will cause an inductive load on the capacitor bank, high temperatures due to high loads will damage the capacitor bank. A switchboard safety automation technology with a microcontroller control system has been proposed to complete this research. Microcontroller control system for switch safety includes Microprocessor (Arduino Nano), light sensor (LDR), temperature sensor (LM35DZ), LCD 16x2 I2C, actuator (fan, buzzer, three-phase network disconnect switch relay), switch (5 VDC relay), ADC As data input. The working principle of the microcontroller is: if the LM35DZ sensor detects the specified temperature, an alarm will be triggered, while the LDR sensor detects a spark, the alarm will be triggered as a danger warning signal and cut off the power grid. Equipment designed to prevent switchboard safety caused by high temperatures or sparks can prevent fires.